Women's experience and attitudes towards menopause and health: descriptive research - Jožefa Gregorin; Jožica Ramšak Pajk (Obzornik zdravstvene nege, 2016)
Introduction: The physiological changes in hormonal levels occurring during perimenopause and postmenopause may affect the health of women. The purpose of the research was to explore the views and attitudes of women of this stage towards menopause, health, healthy lifestyle and some aspects of information regarding menopause. Methods: The study was based on a quantitative and qualitative approach. A semi-structured questionnaire (Cronbach α = 0.813) was used as a research instrument. The open question was interpreted by a qualitative method. A random systematic sample consisted of one hundred female patients, aged 45 to 60 years, attending a private healthcare institution. The survey was conducted in October 2014. The data collected were processed with the software Microsoft Excel and SPSS version 20.0. Results: The self-reported health status of the respondents was good (57.3 %) or very good (22.3 %). The most commonly cited symptoms included hot flushes and night sweats (x̅ = 2.73), sleep problems (x̅ = 2.8), and mental and physical exhaustion (x̅ = 2.70). Information from nurses was never sought by 57.6 % and occasionally by 9.8 % of the respondents, although the interviewees expressed the need for more comprehensive information on the subject. The identified subcategories include a positive attitude and self-confidence, support of the environment, consumer health information and healthy lifestyle. Discussion and conclusion: The research participants have a positive attitude to health, they are aware that there is much they can do to maintain and improve their health. As they also expressed the need to be better informed, the scope of nurses' work in referential out-patient clinics may be extended to menopausal counselling. However, more research on this topic needs to be undertaken.